Marcus Aurelius' Stoicism and its Solution to Overthinking - Muhammad Kevin Saputra; Zaim Rais; Elfi Elfi (Islamic Thought Review, 2023)
This research was library research with overthinking as its material object and the Stoicism of Marcus Aurelius as a formal object. The main problem in this study is how Marcus Aurelius' Stoicism becomes a solution to overthinking. This research used critical analysis and heuristics methods. The data source in this research refers to the book or personal record of Marcus Aurelius, namely Meditations, which is supported by other sources that are closely related to the problems of Stoicism and overthinking. There are some critical points as the solution to the overthinking of Marcus Aurelius' Stoicism, namely, first, living in harmony with nature, where things beyond human control are on the scale of nature. Second, regarding the treatment of others, the actions and words of others are beyond human control, and what should be controlled is their perception. Third, self-restraint is in of control of humans. Everything that comes from out of control will not affect and interfere if in of control can be managed with the argumentation that humans as a whole are human beings that have a ratio; then this is the core of Marcus Aurelius' Stoicism.